Design of intelligent agent on Moodle to automate the learning assessment process - Elhoucine Ouassam; Nabil Hmina; Belaid Bouikhalene (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Assessment is a key element in today’s School system, whether face-to-face or distance learning, as it helps students understand their learning and get feedback on their progress. In addition, distance learning assessment is becoming increasingly popular as it is convenient for students with busy schedules who cannot attend face-to-face assessments. In this paper, we focus on the use of intelligent agents on the Moodle platform to improve the assessment process of distance learning. We present three contributions that aim to improve the developed models: firstly, the digitisation of assessment to collect, store and analyse data; secondly, the adoption of a multi-agent skills assessment environment to automate some assessment tasks; thirdly, the adoption of the leadership and management development (LMD) programme to improve the continuous training of learners by offering greater flexibility, adaptability and relevance to their needs.